Aproveitamento do resíduo de camarão sete-barbas (xiphopernaeus kroyeri) do município de Pirambu/SE para obtenção da astaxantina utilizando técnica de extração com óleos vegetais - Oliveira, Thaciana Vieira de (2018)
With the considerable expansion of the brazilian fishing industry and a greater population demand for food of protein origin, fish production increased and with it also emerged an accelerated generation of waste from the processing of these, which are usually discarded in the environment without any type of treatment. These residues are composed of organic material such as head and shells, rich in bioactive compounds such as carotenoids and their use can increase the economy of the industrial sector, as well as communities that depend economically on fishing and processing, and contribute to mitigate the effects of the degradation of the environment, becoming an alternative so that the fishing activity becomes more sustainable from the technical, environmental, economic and social point of view. In the municipality of Pirambu, the economy is based on fishing, mainly the craft and many families have this activity as a source of subsistence. However, the degradation and silting of the Japaratuba River that cuts through the city has attracted attention from the political authorities and the local population, since it affects the fishing sector of this region, thus arousing the interest of investigation of its causes. It is suspected that one of the possible reasons for the observed environmental degradation may be related to the disposal of organic material from the processing of fish and shrimp in the port that are discarded in the riverbed. In view of the foregoing, the thesis presented had the objective of proposing a way to add value to the shrimp residues processed in the region by extracting the astaxanthin carotenoid using a simple technique with a lower environmental impact. An alternative to the use of sunflower oil and castor oil as solvents in the extraction process was suggested in order to collaborate with the fish industry and the small shrimp beneficiaries of the fishing community of the region of Pirambu-SE, when reviewing their production processes by means of the proposal to take advantage of their waste and reduce the costs generated by their disposal. In addition to optimizing the extraction of astaxanthin in the study of the independent temperature and extraction time variables, in order to increase its concentration and reduce costs, as well as offer the food, pharmaceutical, cosmetic and animal feed industries a new source of natural carotenoids. The results obtained indicate the ideal extraction conditions to obtain a higher carotenoid concentration (18.43mg.g-1) with the use of sunflower oil at an average temperature of 70°C in approximately 5 hours. In the case of castor oil, it was necessary to obtain the values of the parameters wavelength (máx= 435,8nm) and specific extinction coefficient (E = 3056), allowing the calculation of yield of the astaxanthin, considering the ideal conditions indicated to obtain a higher concentration of the carotenoid (14.22 mg.g-1) the time of 10 hours and temperature 80°C. The research made possible the insertion of a technique to obtain a high value-added carotenoid in a simple way with low environmental impact, becoming an income opportunity for shellfish that depend on the shrimp processing, besides mitigating the disposal of a material with high organic load that can cause several environmental, economic and social damages.